Analysis of Sign Language Skills in Improving Communication and Learning for Deaf Children - Fitriyani, Fitriyani; Ainii, Lathifah Qurrotu; Jannah, Raudhatul; Maryam, Siti (Continuous Education: Journal of Science and Research, 2024)
This study uses qualitative methods that aim to identify and describe how sign language skills improve communication and learning for deaf children. Data collection in this study is literature research, namely searching for research data and information through academic articles, books, references, and published materials contained in the library. The results of this study show that one form of communication used by deaf children is nonverbal sign language, and sign language is very important for deaf children who need special support because they cannot communicate like others. Deaf children usually encounter obstacles in the learning process such as when the interaction between the teacher and students is disrupted and students may not be able to understand the content delivered by the teacher. To achieve optimal learning, appropriate teaching methods and sign language are needed, namely SIBI (Indonesian Sign Language System) and Bisindo. Such methods help deaf students acquire language skills, improve communication skills, and facilitate the exchange of materials between teachers and deaf students. Therefore, in communicating with healthy people, it is necessary to communicate using sign language that can be understood by deaf people.